1997
DOI: 10.1073/pnas.94.19.10450
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective activity of a new class of steroidal inhibitors of the N -methyl- d -aspartate receptor

Abstract: Release of the excitatory neurotransmitter glutamate and the excessive stimulation of N-methyl-Daspartate (NMDA)-type glutamate receptors is thought to be responsible for much of the neuronal death that occurs following focal hypoxia-ischemia in the central nervous system. Our laboratory has identified endogenous sulfated steroids that potentiate or inhibit NMDA-induced currents. Here we report that 3␣-ol-5␤-pregnan-20-one hemisuccinate (3␣5␤HS), a synthetic homologue of naturally occurring pregnanolone sulfat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 18 publications
8
67
0
Order By: Relevance
“…Neurosteroids, and sulfated neurosteroids in particular, are present at relatively low concentrations in the rat brain (Higashi et al, 2003;Liu et al, 2003). Nonetheless, when PS is administered at femtomole concentrations by intracerebroventricular injection to rodents, processes involving the NMDA receptor are affected (Flood et al, 1995;Mathis et al, 1996;Meziane et al, 1996;Weaver et al, 1997). In contrast, in electrophysiological experiments, much higher (micromolar) concentrations of the steroids are required to achieve modulatory effects on recombinant NMDA receptors (Mukai et al, 2000;Malayev et al, 2002).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Neurosteroids, and sulfated neurosteroids in particular, are present at relatively low concentrations in the rat brain (Higashi et al, 2003;Liu et al, 2003). Nonetheless, when PS is administered at femtomole concentrations by intracerebroventricular injection to rodents, processes involving the NMDA receptor are affected (Flood et al, 1995;Mathis et al, 1996;Meziane et al, 1996;Weaver et al, 1997). In contrast, in electrophysiological experiments, much higher (micromolar) concentrations of the steroids are required to achieve modulatory effects on recombinant NMDA receptors (Mukai et al, 2000;Malayev et al, 2002).…”
Section: Introductionmentioning
confidence: 85%
“…The interaction between PS (at nanomolar concentrations) and ifenprodil as seen in our experiments may thus involve other site(s) of action for PS compared with those studied at much higher concentrations. These targets can represent high-and low-affinity sites for some neurosteroids where the former sites may mediate in vivo effects seen after administration of very low amounts of these compounds (Flood et al, 1995;Mathis et al, 1996;Meziane et al, 1996;Weaver et al, 1997). We propose that PS and 3␣5␤S at physiological concentration can change ifenprodil binding by converting the receptor site from a one-site state into a twosite state.…”
Section: Molecular Mechanisms For Neurosteroids At Nr1/nr2bmentioning
confidence: 99%
“…Synthetic analogs of neuroactive steroids, which are more resistant to metabolism and better able to cross the blood-brain barrier, are now being investigated for potential use as anxiolytics, anesthetics, and anticonvulsants (Weaver et al, 1997;Gasior et al, 1999). One synthetic neurosteroid, pregnanolone hemisuccinate, produces sedation in mice and rats (Weaver et al, 1997), raising the possibility that it acts either by inhibiting the NMDA receptor or by crossing the bloodbrain barrier and undergoing metabolism to pregnanolone. Synthetic neurosteroids bearing a hemisuccinate group are more resistant to hydrolysis than the corresponding sulfate esters and are partly unionized at physiologic pH, allowing ready passage across the blood-brain barrier.…”
Section: F Neuroactive Steroids As Neuromodulators Of Transmissionmentioning
confidence: 99%
“…Neurosteroids such as pregnanolone sulfate, which enhances cognition, positively modulates NMDAR function, and stimulates NMDAR trafficking to the cell surface (Wu et al, 1991;Kostakis et al, 2013), may represent one such endogenous mechanism for linking fearful stimuli and the emotional response subject to therapeutic manipulation (Plescia et al, 2013). Neuroactive steroids, such as pregnanolone sulfate and pregnanolone hemisuccinate, which inhibit glutamatergic neurotransmission by negatively modulating NMDAR function (Park-Chung et al, 1994) and may also exhibit mixed function by serving as both a negative modulator of the NMDAR and a prodrug for pregnanolone (a positive modulator of GABA A R) delivery across the blood-brain barrier, may also represent a novel platform for discovery (Weaver et al, 1997(Weaver et al, , 2000.…”
mentioning
confidence: 99%
“…Estrogen increases the number of surviving cells following ischemia (Liu et al, 2009;Merchenthaler et al, 2003;Platha et al, 2004;Wappler et al, 2010), reduces excitotoxicity (Connell et el., 2007;Herson et al, 2009;Weaver et al, 1997), inflammation (Herson et al, 2009 ;Stein, 2001;Suzuki et al, 2007), moderates blood-brain barrier dysfunction (Liu et al, 2005), is antioxidant (Connell et el., 2007), increases cerebral blood flow (Herson et al, 2009;Hurn et al, 1995;Pelligrino et al, 1998), reduces spontaneous postischemic hyperthermia (Platha et al, 2004), etc. Cerebral ischemia studies in ER-and ER-KO mice models, and pharmacological receptor inhibition have shown that ER-is the primary mediator of neuroprotection.…”
Section: Estrogen: Afforded Protection and Plasticity Following Brainmentioning
confidence: 99%